2019
DOI: 10.1039/c9py00810a
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of hybrid micelles with enhanced permeability for drug delivery via a diethoxymethylsilyl-based crosslinking strategy

Abstract: A novel reducible silica monomer, DESSPMA with diethoxysilyl groups for in situ crosslinking to give a lower crosslinking density and greater permeability than the triethoxysilyl-based TESSPMA was developed to realize enhanced therapeutic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Hence, it is most likely that for the micelle-based drug delivery systems, the promoted drug release due to the loss of micelle stability outperforms enhanced drug encapsulation and compromised drug diffusion because of the formation of hydrophobic aggregates. The increased cumulative drug release because of the loss of micelle stability was previously observed as well. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is most likely that for the micelle-based drug delivery systems, the promoted drug release due to the loss of micelle stability outperforms enhanced drug encapsulation and compromised drug diffusion because of the formation of hydrophobic aggregates. The increased cumulative drug release because of the loss of micelle stability was previously observed as well. , …”
Section: Resultsmentioning
confidence: 99%
“…The increased cumulative drug release because of the loss of micelle stability was previously observed as well. 34,35 In Vitro Cellular Uptake and Competition Study. FAmediated cellular uptake was further quantified in HeLa cells (folate receptor (FR)+) using flow cytometry (FCM) analysis (Figure 7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Esterification of 2-hydroxyethyl disulfide with acyl chloride, acyl bromide, and carboxylic acid has been reported to generate various bioreducible agents as promising monomers, 27,28 crosslinking agents, 29,30 initiator, 31 and chain transfer reagents [28][29][30][31][32] for the construction of valuable biomaterials. Therefore, 2-hydroxyethyl disulfide was used as a precursor to prepare a glutathione (GSH)-responsive HSEMA-g-PCL macromonomer in this study (Scheme S1 †).…”
Section: Synthesis and Characterization Of The Hsema-g-pcl Macromonomermentioning
confidence: 99%
“…Of the reported stimuli approaches, the application of GSH-sensitive polymers containing disulfide bridges is of particular importance owing to the distinct difference in the GSH levels between normal cells (≈2 mm) and specific tumor cells (≈10 mm). [36] The previously fabricated disulfide bridges-contained organic/inorganic hybrid nanomedicines [37,38] and hyperbranched nanomedicines [39] showed that the intracellular cleavage of disulfide links promotes the destabilization of nanomedicine and subsequently intracellular drug release in tumor cells for enhanced therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%